Evaluation of pant characteristics and physiological performance of mungbean (Vigna radiata (L.) Wilczek) genotypes under salt stress (Journal of the Asiatic Society of Bangladesh, Science, 2023)
Mungbean is a delicious popular pulse crop whose yield is hampered by biotic and abiotic factors. Salinity is considered serious abiotic stress that hinders growth and yield drastically. To find out the response features of salinity tolerance in mungbean, a series of experiments were carried out in the Department of Crop Botany of BSMRAU. The experiment was performed in the greenhouse of the Crop Botany department using nutrient solution under hydroponics conditions. Initially, fifty-two mungbean genotypes were used in the experiment to screen out a susceptible and tolerant genotype. The results indicated that salinity affected the plants at various morphological characteristics namely plant height, and dry matter of root, stem, and fruit. The genotypes were placed in four groups based on their performance in salinity. A higher quantity of proline with a lower amount of Malon-dialdehyde was observed with the increase in salinity. Chlorophyll content increased initially and after that declined sharply. The susceptible genotype resulted in a sharp decline of chlorophyll and increased proline content which reflected the 1accumulation of root and shoot dry matter, and consequently, the total dry matter content compared to that of the tolerant genotype.J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 97-110, June-December 2022